Pyrene and nile red fluorescence probes for in‐situ study of polarity and viscosity of soil organic coatings implicated in soil water repellency. (12th January 2020) - Balshaw, Helen M.; Douglas, Peter; Davies, Matthew L.; Doerr, Stefan H.
Abstract: Soil water repellency, that is, the reduced ability of soils to absorb water, is thought to be caused by organic coatings with predominantly non‐polar properties on soil particle surfaces. Given the important role of particle surface polarity in determining soil water repellency, we explored the use of fluorescent probes as a method for the direct in‐situ determination of the distribution and polarity of organics on bulk soil surfaces, and of their molecular mobility. We used nile red and pyrene, which have both been used successfully as environmental probes in previous studies, but have not been applied before to bulk soils. The probes were either (a) co‐deposited with other organics known to induce water‐repellent behaviour with acid‐washed sand to produce 'model soils' or (b) adsorbed directly onto sandy soils that were naturally water repellent to different degrees, and studied using fluorescence microscopy and steady‐state and time‐resolved fluorescence. Reliable measurements could be made using pyrene as an in‐situ probe on both model and natural soils, and a viscosity/mobility probe on model soils, whereas nile red was found not to be a useful probe. On model soils, made using hexadecane (HEX), octadecane (OCT) or stearic acid (SA) on acid‐washed sand, pyrene excimer formation kinetics showed a decrease in environment mobility as the organic layer changes from a liquid through to a hard wax. Spectra from pyrene adsorbed to natural soils indicated varying environmental polarity and heterogeneity within the soil samples studied. Highlights: Exploration of in‐situ fluorescent probes to study polarity and viscosity of organics on soils. Fluorescent probes have never been used in situ on bulk soils before. Pyrene probe shows variation in mobility, polarity and heterogeneity of organics on soils. Pyrene is a useful in‐situ fluorescent probe of polarity and mobility of organics on soils.